Kinematic differences between front crawl sprint and distance swimmers at sprint pace - McCabe, C. B.; Psycharakis, S.; Sanders, R. (Journal of Sports Sciences, 2011)
The purpose of this study was to use three-dimensional methods to determine whether there are distinct kinematic differences between sprint and distance front crawl swimmers when swimming at a sprint pace. Seven sprint and eight distance specialists performed four 25-m sprints through a 6.75-m3 calibrated space recorded by six gen-locked cameras. The variables of interest were: average swim velocity, stroke length, stroke frequency, upper limb and foot displacement, elbow angle, shoulder and hip roll angles, duration of stroke phases, and the time corresponding to particular events within the stroke cycle relative to hand entry. Differences between sprint and distance swimmers were assessed with an independent t-test for each variable, in addition to effect size calculations. Differences between sprint and distance front crawl swimmers were generally small and not significant when swimming at a sprint pace. Differences were limited to temporal aspects of the stroke cycle. These findings suggest that coaches should not train sprint and distance specialists differently in terms of technique development.